Diversity, transformative knowledge, and civic education selected essays - Banks, James A. (Routledge, Taylor & Francis Group, 2020)
The essays collected in this book, by James A. Banks, a foundational figure in the field of multicultural education, illuminate the interconnection between the author's work on knowledge construction and civic education. In pieces both poignant and personal, Banks shares some of his most groundbreaking and innovative work. Diversity, Transformative Knowledge, and Civic Education aims to unpack the "citizenship-education dilemma," whereby education programs strive to teach students democratic ideals and values within social, economic, political, and educational contexts that contradict justice, equality, and human rights. For change to take place, students need to internalize democratic values, by directly experiencing them in transformative classrooms and schools that are envisioned and described in this book. Drawn from Banks' formidable canon, this collection highlights the conceptual, curricular, and pedagogical issues related to this dilemma, and signals a fundamental shift toward transformative citizenship education. Students, scholars and educators in the fields of multicultural education, civic education, social studies education, comparative education, and the foundations of education will find this book to be a valuable resource for discussion and discovery